Investigation Of Grid Reader Network Based Positioning And Tracking For RFID With Indoor Coverage - Reza, Ahmed Wasif (2009)
This study proposes highly accurate square grid and hexagonal grid based positioning and tracking techniques mainly for use indoor and includes performance comparison of both of these grids.